The impact of Ad overloads perception in social media on Ad avoidance behavior: the mediating effect of social media fatigue and goal impediment - EssaTayeb, Mesud; Chebbi, Taha; Badawi, Aisha; Ali Toumi, Jamal; Louail, Bilel (Zielona Góra: Faculty of Economics and Management Press)
Consumers increasingly employ ad-blocking tools and exhibit resistance to traditional marketing tactics, causing significant losses for digital publishers. This study examines the effects of ad clutter and ad intrusiveness on advertising avoidance behavior among social media users, emphasizing the mediating roles of perceived goal impediment and social media fatigue. Utilizing reactance theory and cognitive load theory, the research reveals that ad clutter negatively impacts user attention and recall, contributing to heightened ad avoidance.
Keywords: ad clutter; ad intrusiveness; perceived goal impediment; social media fatigue; advertising avoidance